Truth and transparency : undercover investigations in the twenty-first century / Alan K. Chen, Justin Marceau. - Chen, Alan; Marceau, Justin (Cambridge University Press, 2023)
Truth and transparency are central to an informed democracy. This book explores how undercover investigations, though controversial, can contribute to democracy by exposing wrongdoers. Through empirical research and doctrinal study, it examines in depth the legality of, and public opinion about, such investigations in the US.